Performance analysis of new liquid cooling topology and its impact on data centres - Hnayno, Mohamad; Chehade, Ali; Klaba, Henryk; Bauduin, Hadrien; Polidori, Guillaume; Maalouf, Chadi (Applied Thermal Engineering, 2022)
A large amount of the energy consumed by data centres is related to the cooling demand. The use of optimised liquid cooling technology enables one to increase the water inlet temperature and the water temperature difference of a data centre. Accordingly, the energy consumption of the data centre infrastructure can be reduced by appropriately utilising free cooling available on-site. This paper presents an experimental investigation and performance analysis conducted on a novel liquid-cooled topology deployed within OVHcloud data centres. A rack cooling system based on a combination of close-coupled cooling and direct-to-chip cooling is presented. The experimental setup used comprised five information-technology racks with operational servers under different temperature profiles (15 K and 20 K) for two thermal conditions (27 °C and 35 °C). The results indicated a repartitioning of thermal load absorption between close coupled cooling and direct-to-chip cooling to approximately 56% and 44%, respectively. Thereby, air was still necessary as a coolant for the data centre. A temperature difference was validated for all the information technology racks, whereas the 20 K temperature-difference profile was validated with the proposed new rear-door heat exchanger (RDHX) configuration. In addition, a performance analysis was performed on a data centre of 600 kW cooled with this topology for three heat rejection systems (mechanical cooling system using chillers, indirect free cooling with evaporative cooling, and hybrid chillers with intelligent dry coolers) under four climatic conditions. Indirect free cooling combined with an evaporative cooling system showed optimal energy savings. A reduction in annual power consumption by 89% was achieved compared with the mechanical cooling system at four locations where data centres were located. The cooling partial power usage effectiveness of data centre was reduced by at least 16% with respect to mechanical cooling. An increase in the temperature difference of the information technology racks from 15 K to 20 K caused a reduction in the water usage effectiveness of the data centre by at least 40%. An increase in the temperature of the cold water supplied to the data centre by 5 K caused a reduction in water usage effectiveness and annual water consumption by at least 30% and 47%, respectively.
Keywords: Data centre cooling; Energy; Free cooling; Heat transfer; Liquid cooling